The influence of the educational system on the level of personal anxiety of the Waldorf schools and High schools students - Передерій, Ольга Леонідівна (Pedagogy of Higher and Secondary Education, 2017)
The problem of students anxiety attracts the attention of many researchers. High level of anxiety affects students’ stydying, their social adaptation, their health and psychological state. The theoretical analysis of the influence of the educational system on the level of students’ personal anxiety is made in the article. The most significant causes of anxiety of different age groups have been given. Thus, the main factors affecting the level of emotional stability and students anxiety are: excessive theoretical materials, a huge amount of homework, imbalance between the school year structure, curriculum and students age characteristics, lack of teachers competence who cannot use modern teaching methods and techniques, the relationship between students and teachers. The basic differences in anxiety between Waldorf and secondary schools pupils have been studied, and it has been found that the anxiety level of Waldorf schools students is much lower. The problem of emotional instability and high school students anxiety can be resolved under the following conditions: learning process is determined according to the individual characteristics of students; the amount of homework is limited; training through organized activities and gaming methods; teacher uses modern teaching methods and techniques; teacher supports each student’s confidence and motivates for learning; use possibilities of art subject to stabilize students emotional state and anxiety; much emphasis is made on students’ physical skills and a healthy lifestyle; school education is conducted on democratic principles.